2021
DOI: 10.1002/ppul.25374
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of impulse oscillometry for asthma exacerbations in childhood: A systematic review and meta‐analyses

Abstract: Objective: Several studies have explored the predictive value of impulse oscillometry (IOS) for asthma exacerbations in childhood, but its specific parameters are still unclear. Therefore, we designed this meta-analysis to determine the related indicators of acute asthma attacks.Methods: A comprehensive literature search was performed on July 9, 2020 based on PubMed, Embase, and Web of Science database. Weighted mean differences (WMDs) were calculated using fixed-or random-effects models.Results: A total of 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…X 5 and A X reflect the elasticity of the peripheral airways, while X 20 reflects the elasticity of larger, central airways, 27 with the changes observed indicating changes in lung compliance, that may reflect reduced dynamic hyperinflation and gas trapping 28 . Importantly, both X 5 and A X predict asthma exacerbations and loss of asthma control in children with asthma 29 . Airway resistance reflects airway obstruction, 27 and R 5 ‐R 20 is proposed to reflect peripheral airways 27 .…”
Section: Discussionmentioning
confidence: 99%
“…X 5 and A X reflect the elasticity of the peripheral airways, while X 20 reflects the elasticity of larger, central airways, 27 with the changes observed indicating changes in lung compliance, that may reflect reduced dynamic hyperinflation and gas trapping 28 . Importantly, both X 5 and A X predict asthma exacerbations and loss of asthma control in children with asthma 29 . Airway resistance reflects airway obstruction, 27 and R 5 ‐R 20 is proposed to reflect peripheral airways 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Small airway disease usually results in the frequency dependence of resistance (Fres), that is, an increased difference between R5 Hz and R20 Hz (R5–20 Hz) and decrease in Xrs. A recent systematic review with meta-analyses showed that R5 Hz, X5 Hz, Fres and reactance area (AX) may predict asthma exacerbations in children [20 ▪▪ ].…”
Section: Impulse Oscillometrymentioning
confidence: 99%
“…The Global Initiative for Asthma (GINA) has made recommendations for early diagnosis and good control based on symptoms and conventional spirometry to improve asthma outcomes (6). Impulse oscillometry (IOS) is an effort-independent method for measuring respiratory system resistance (R) and reactance (X), which is suitable for younger children unable to receive spirometry (7)(8)(9). Increasing evidence shows that IOS indicator with R5 (resistance at 5 Hz) may better predict asthma exacerbations or loss of control in children with asthma (8).…”
Section: Introductionmentioning
confidence: 99%
“…Impulse oscillometry (IOS) is an effort-independent method for measuring respiratory system resistance (R) and reactance (X), which is suitable for younger children unable to receive spirometry (7)(8)(9). Increasing evidence shows that IOS indicator with R5 (resistance at 5 Hz) may better predict asthma exacerbations or loss of control in children with asthma (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation